The Variety Of Quantitative And Qualitative Character Of Five Varieties Of Mung Bean (Vigna radiata) - Franklin Dotulong; Maria Y.M.A. Sumakud; Sesilia A. Wanget; Ventje Pangemanan (COCOS, 2013)
ABSTRACTQuantitative character was seen as a form of continuous distribution, observed by measuring, had many controller genes, influenced by environmental factors very easily and selected through data analysis. Qualitative character was seen as a form of rigid distribution, observed visually, had one or two controller genes, influenced by environmental factors very scarcely and selected visually. Genetic variation was a variation that happened by the changes of genetic substances which were permanent and were always inherited to its heredity. This research was conducted in Winorangian Village, Tombatu Subdistrict, Minahasa Tenggara Municipality. The objective of this research was to study about the variety of quantitative and qualitative character of five varieties of mung bean.This research was done by using Randomized Block Design (RBD), with five ways of handling and four experiments. As research instruments, the researcher used five varietiesof mung bean: Sriti Variety (V1), Merak Variety (V2), Kenari Variety (V3), Perkutut Variety (V4), and Betet Variety (V5).The research finding showed that those five varieties of mung bean had narrow type of genotype type, where as the genotype type is lesser or equals to the double of the number of the standard deviation of genotype type. It indicated that the inherited character from the predecessor was very strong (homogen) and influenced by environmental factors very scarcely.Keywords: Quantitative Character, Qualitative Character, Genetics Variation, Mung Bean